2004
DOI: 10.1111/j.1365-2567.2004.01863.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired chemokine‐induced migration during T‐cell development in the absence of Jak 3

Abstract: SUMMARYThe arrival of bone marrow T-cell progenitors to the thymus, and the directed migration of thymocytes, are thought to be regulated by the expression of chemokines and their receptors. Recent data has shown that the Jak ⁄Stat signalling pathway is involved in chemokine receptor signalling. We have investigated the role of Jak 3 in chemokine-mediated signalling in the thymus using Jak 3 -⁄ -mice. These mice show defects in T-cell development, as well as in peripheral T-cell function, resulting in a hypopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
63
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 41 publications
5
63
1
Order By: Relevance
“…CXCR4 Signaling Is Not Affected by Jak2 and Jak3 in HEK293 Cells-Using an inhibitor that blocks both Jaks as well as other kinases, previous studies have concluded that Jaks are essential for chemokine signaling (18,20,22,27,28). However, the use of pharmacologic inhibitors may lead to erroneous conclusions and therefore need to be verified by genetic approaches.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CXCR4 Signaling Is Not Affected by Jak2 and Jak3 in HEK293 Cells-Using an inhibitor that blocks both Jaks as well as other kinases, previous studies have concluded that Jaks are essential for chemokine signaling (18,20,22,27,28). However, the use of pharmacologic inhibitors may lead to erroneous conclusions and therefore need to be verified by genetic approaches.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study that examined CXCL12 signaling in murine Jak3-deficient thymocytes concluded that chemotaxis is impaired (27). The authors also concluded that CXCR4 expression was normal at the level of mRNA.…”
Section: Figmentioning
confidence: 96%
See 1 more Smart Citation
“…G-protein dependent activation of CXCR4 also induces several MAPKs signaling pathways such as ERK, JNK and P38 (Bajetto A et al, 2001;Han Y et al, 2001a;Han Y et al, 2001b;Fernandis AZ et al, 2004;Alvarez S et al, 2005). In addition, CXCL12/CXCR4 activates the Janus kinase-signal transducer and activator of transcription (JAK/STAT) pathway in a PTX independent manner (Vila- Coro AJ et al, 1999;Soriano SF et al, 2003;Soldevila G et al, 2004). CXCL12/CXCR4 signaling is regulated by G protein-coupled receptor kinases (GRKs) and β-arrestins (Fig.…”
Section: Cxcl12/cxcr4 Signaling Pathwaysmentioning
confidence: 99%
“…ELAVL1 codes for a RNA-binding factor expressed in a wide variety of cells and involved in RNA degradation (King et al, 2000). CCL25 encodes for a chemokine molecule (Soldevila et al, 2004). ANGPL4 codes for a factor promoting angiogenesis and is overexpressed in several tumours (Tait and Jones, 2004).…”
mentioning
confidence: 99%